Sitafloxacin Expresses Potent Anti-Mycobacterium abscessus Activity - He, Siyuan; Guo, Qi; Zhao, Lan; Xu, Liyun; Fan, Junsheng; Wu, Wenye; Zhang, Zhemin; Li, Bing; Chu, Haiqing (Frontiers in Microbiology, 2022)
Therapeutic options for treating Mycobacterium abscessus infections are extremely limited; quinolones are important. The in vitro anti-M. abscessus activities of nine quinolones, emphasizing sitafloxacin, were investigated. Antimicrobial susceptibility testing was performed on 10 non-tuberculous mycobacterium reference strains and 194 clinical, M. abscessus isolates. The activity of sitafloxacin against intracellular M. abscessus residing within macrophages was also evaluated. A checkerboard assay was conducted to determine synergy between sitafloxacin and 10 clinically important antibiotics. Among the nine quinolones tested, sitafloxacin exhibited the greatest anti-M. abscessus activity with MIC50 and MIC90 of 1 and 2 mg/L, respectively. Sitafloxacin exerted a bacteriostatic effect on M. abscessus and inhibited the intracellular growth of M. abscessus at concentrations equivalent to clarithromycin. No antagonism between sitafloxacin and 10 clinically important anti-M. abscessus antibiotics was evident. In summary, sitafloxacin exhibited a significant advantage relative to other quinolones in inhibiting the growth of M. abscessus in vitro, suggesting the potential inclusion of sitafloxacin in new strategies to treat M. abscessus infections.